2018
DOI: 10.1002/mbo3.743
|View full text |Cite
|
Sign up to set email alerts
|

A change in the bacterial community of spider mites decreases fecundity on multiple host plants

Abstract: Bacterial symbionts may influence the fitness of their herbivore hosts, but such effects have been poorly studied across most invertebrate groups. The spider mite, Tetranychus truncatus, is a polyphagous agricultural pest harboring various bacterial symbionts whose function is largely unknown. Here, by using a high‐throughput 16S rRNA amplicon sequencing approach, we characterized the bacterial diversity and community composition of spider mites fed on five host plants after communities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 83 publications
1
36
0
Order By: Relevance
“…In T. truncatus spider mites, Zhu et al () showed that antibiotic treatment affects the composition of the bacterial community even after more than 20 generations without antibiotics. In particular, bacteria from different families increased in proportion in tetracycline‐treated mites in absence of the Anaplasmataceae (which includes Wolbachia ).…”
Section: Discussionmentioning
confidence: 99%
“…In T. truncatus spider mites, Zhu et al () showed that antibiotic treatment affects the composition of the bacterial community even after more than 20 generations without antibiotics. In particular, bacteria from different families increased in proportion in tetracycline‐treated mites in absence of the Anaplasmataceae (which includes Wolbachia ).…”
Section: Discussionmentioning
confidence: 99%
“…Microbial community homeostasis, which is needed to maintain normal host physiology, can be disturbed by several factors, such as temperature, weather and changes in Correspondence: Xiao-Yue Hong, Department of Entomology, Nanjing Agricultural University, Nanjing 210095, China. Tel: +86 25 84395339; fax: +86 25 84395339; Email: xyhong@njau.edu.cn the host (Zhu et al, 2018). Antibiotic treatment severely alters the size and composition of the microbial community in humans and domesticated animals (Huse et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…However, antibiotics do not affect Wolbachia only, but also the entire bacterial community in hosts (e.g. Lehman et al 2009;Zhu et al 2018;Zouache et al 2009), which raises the necessity to assess the potential effect of the antibiotic treatment per se.…”
Section: Discussionmentioning
confidence: 99%
“…In T. truncatus spider mites, Zhu et al (2018) showed that an antibiotic treatment (tetracycline hydrochloride during three generations) strongly affects the composition of the bacterial community even after more than 20 generations without antibiotics. In particular, these authors showed that bacteria from different families strongly increased in proportion in tetracycline-treated mites in absence of the Anaplasmataceae The apparent facilitation of B. bassiana by Wolbachia in the TOM population may also be due to…”
Section: Discussionmentioning
confidence: 99%